Inventário de exemplares arquitetônicos do município de Palmeira das Missões-RS: a cidade e a memória (1874-1950) - Lagomarsino, Kamila Medeiros (2023)
This dissertation comprises the Architectural and Material Heritage area, based on the Material Heritage Preservation line, from the Federal University of Santa Maria, through the Post Graduate Program about Cultural Heritage. The aim of this research is the development of an Architectonic Heritage Inventory from the municipality of Palmeira das Missões. The inventory is a document that stands out as a tool that enables preservation, maintaining the collective memory and providing the building’s appreciation. This inventory will be made through a survey of the buildings selected with the historical and cultural criteria established in this research, interconnecting them to the municipality formation. For the selection and framework of the buildings in this exploratory research and qualitative approach work, a time frame between 1874 and 1950 was considered, likewise the municipality's historic-cultural relevance and its morfologic-architectonic profile. The buildings’ inventorying will be made through physical surveys, private record and photographic analysis in inventory files. From the analysis that will provide the creation of an inventory, it aims to share and value the architectural heritage, besides contributing to urban memory. It is necessary to document the selected buildings for its recognition and history preservation. The architectural production will be recognized through an architectural buildings’ registration. This research’s product will be a booklet about the city’s architecture containing the identification and registration from examples, and the architectonic, historical and constructive aspects that can be enjoyed by an audience with ages starting from 10 years old.